Surgical Treatment of Siewert II Gastroesophagel Junction Adenocarcinoma: Esophagectomy or Gastrectomy? Review - Imbrasaitė, Ugnė; Giršvildaitė, Dovilė; Baušys, Rimantas; Baušys, Augustinas (Lietuvos chirurgija, 2022)
Introduction. Surgery is the only curative treatment option for patients with gastroesophageal junction (GEJ) adenocarcinoma. These tumors can be resected by gastrectomy or esophagectomy depending on tumor localization. Although, both surgeries are available for Siewert type II GEJ cancer, it remains unknown which one is superior. This review summarizes current evidences on the optimal surgical approach for Siewert type II GEJ adenocarcinoma. Methods. The literature search was performed within the PubMed database and 9 studies comparing gastrectomy and esophagectomy for Siewert type II GEJ adenocarcinoma were included. The outcomes of interest included: length of surgery, numbers of retrieved lymph nodes, resection margins, postoperative morbidity and mortality, hospitalization time, 5-year overall, and disease-free survival rates. Results. Current studies do not favor any type of surgery in terms of length of the surgery, R0 resection rate, or postoperative morbidity. There is some tendency towards higher anastomotic leakage and postoperative surgical site infections rate after gastrectomy, while a higher incidence of pneumonia after esophagectomy. Similar, available studies suggest, that esophagectomy may lead to improved long-term outcomes. Conclusions. There is a lack of high-quality studies comparing gastrectomy and esophagectomy for Siewert type II GEJ adenocarcinoma. Esophagectomy may lead to improved long-term outcomes, but this preliminary data has to be confirmed in large, randomized control trials.
Keywords: esophagectomy; gastrectomy; gastroesophageal junction adenocarcinoma; gastroesophageal junction tumors; Siewert classification.